Reduced insulin use and diabetes complications upon introduction of SGLT-2 inhibitors and GLP1-receptor agonists in low- and middle-income countries: a microsimulation - Ali, Mohammed K.; Bärnighausen, Till; Teufel, Felix (PLoS medicine, 2025)
Background Diabetes mellitus, particularly type 2 diabetes, is a growing health concern in low- and middle-income countries (LMICs). The potential impact of newer diabetes medications, such as glucagon-like peptide 1 (GLP-1) receptor agonists and sodium-glucose co-transporter-2 (SGLT-2) inhibitors, on insulin dosage and health outcomes in these settings is not well understood. Methods and findings We developed a microsimulation model to estimate the impact of treating patients with type 2 diabetes who use insulin with GLP-1 receptor agonists or SGLT-2 inhibitors in LMICs. The model utilized data from the Global Health and Population Project on Access to Care for Cardiometabolic Diseases (HPACC) dataset, encompassing surveys from 79 countries and clinical trial data to estimate insulin dose reduction. We incorporated weight-based insulin dosing formulas and hazard ratios for severe hypoglycemia, cardiovascular and renal outcomes, side effects of new therapies, and mortality. The primary outcome was the change in insulin dosage, and secondary outcomes were disability-adjusted life years (DALYs) lost per 1,000 person-years by diabetes complication (micro- and macro-vascular). Our results indicate that the addition of GLP-1 receptor agonists or SGLT-2 inhibitors could reduce insulin dosage by 8.2 IU/day (IQR: 6.9, 9.5) and 5.3 IU/day (IQR: 4.5, 6.2), respectively. The median DALYs lost per 1,000 person-years decreased from 2.20 (IQR: 1.49, 4.02) to 1.01 (IQR: 0.61, 1.86) with GLP-1 receptor agonists and 1.25 (IQR: 0.81, 2.29) with SGLT-2 inhibitors. Primary benefits arose from weight loss, decreased cardiorenal disease, and decreased mortality, with smaller DALY benefits from the prevention of severe hypoglycemia. Key limitations include the inability to differentiate between type 1 and type 2 diabetes in some datasets and reliance on assumptions from clinical trials conducted primarily in high-income countries. Conclusions The introduction of GLP-1 receptor agonists and SGLT-2 inhibitors for managing type 2 diabetes in LMICs could significantly reduce insulin dosage and associated health risks, leading to improved outcomes and reduced disability. These findings suggest that expanding access to these newer diabetes medications in LMICs could have substantial public health benefits.